Gaining competitiveness advantage of Islamic credit card among Muslim customer in Malaysia - Haque, A. K. M. Ahasanul; Robel, S. D.; Abdullah, Kalthom (Universiti Teknologi MARA, 2018)
Malaysia is considered as a global hub of Islamic banking and finance. To upgrade banking fac ilities, Malaysian banks provide various functions and services to its consumers. One of the most popular of these services is the credit card which prov ides consumers with an innovative and fl exible insight on banking services. Thus, in th e current yea rs, both Islamic and conventional banks in Malaysia offer credit card services to its population. Numerous banks in Malaysia face chall enges to compete within the conven tional credit card whi le working towards atta ining the highest market share in Islamic credit cards. In order to be successful in the credit card business, there is no altern ative for Islamic credit cards but to develop sustainable competiti ve advantage. This study explores the increasing competitiveness of the Islamic credit card among Muslim consumers in Malaysia. Various ex isting research and publications have contributed to the coll ect ion of secondary data. The conceptual framework developed used for gaining the competiti ve advantage of Islamic credit card has been derived from existing literature in the Malaysian context. Islamic credit cards' competitiveness over the conventional credit card to attract Muslim consumers and success in Malaysia is contrasted in this study. Subsequently, this study will also facilitate the banks by allowing them to gain the competitive advantage in Islamic credit card usage to capture the highest market share. In the meantime, this study wi ll also be a valuable add ition to both academies and consumers alike.